Ownership structure and dividend payout of listed firms in Bangladesh: An application of the Tobit model - Hosain, Md Zakir; Islam, K M Zahidul; Uddin, Md Parvez (Asian Journal of Economic Modelling, 2026)
This study investigates the impact of ownership structure on the dividend payout of firms in Bangladesh over a fourteen-year period from 2008 to 2021. It considers managerial ownership, institutional ownership, and individual ownership, along with eight control variables, to identify their effects on dividend payout. The research employs multiple techniques to analyze the collected panel data, including the Tobit pooled and Tobit random effect models. To improve the efficiency of these models, the study applies bootstrap standard error estimation. The results reveal that institutional ownership (INSOW) is positively associated with dividend payout, indicating the influential role of institutional investors in dividend decisions. These findings are significant for investors, researchers, policymakers, and company management regarding dividend payout strategies. The study provides empirical validation for agency theory by demonstrating that institutional investors reduce monitoring costs, offering a clear policy impetus for regulators to encourage greater institutional ownership as a mechanism to protect minority shareholders. Additionally, it offers valuable insights into how various ownership structures influence dividend decisions in emerging countries, specifically within the context of Bangladesh. This research fills a notable gap in the existing literature on corporate payouts. The findings have important implications for investors, providing a framework for both individual and institutional investors to identify stable investment opportunities.